Habitat Management: A Tool to Modify Ecosystem Impacts of Nitrogen Deposition? - S.A. Power; C.G. Barker; E.A. Allchin; M.R. Ashmore; J.N.B. Bell (The Scientific World Journal)
Atmospheric nitrogen deposition has been shown to affect both the structure and the function of heathland ecosystems. Heathlands are semi-natural habitats and, as such, undergo regular management by mowing or burning. Different forms of management remove more or less nutrients from the system, so habitat management has the potential to mitigate some of the effects of atmospheric deposition. Data from a dynamic vegetation model and two field experiments are presented. The first involves nitrogen addition following different forms of habitat management. The second tests the use of habitat management to promote heathland recovery after a reduction in nitrogen deposition. Both modelling and experimental approaches suggest that plant and microbial response to nitrogen is affected by management. Shoot growth and rates of decomposition were lowest in plots managed using more intensive techniques, including mowing with litter removal and a high temperature burn. Field data also indicate that ecosystem recovery from prolonged elevated inputs of nitrogen may take many years, or even decades, even after the removal of plant and litter nitrogen stores which accompanies the more intensive forms of habitat management.